Formação teórica, metodológica e prática dos conceitos de revisão e reescrita no PIBID de língua portuguesa - Beloti, Adriana (2016)
The process of theoretical, methodological and practical formation on text revision and rewriting with teachers in initial formation is provided. Teachers participated in the Institutional Scholarship Program for Teaching Initiation (PIBID), sub-project Portuguese Language of the Universidade Estadual do Paraná (Campo Mourão, Brazil). We are convinced that such formation guides and makes up effective teaching practices with the production of written texts and contributes towards text revision and rewriting processes of their future students through the development of their writing and linguistic-discursive capacities. The thesis aims at understanding how the theoretical-methodological formation on the revision and rewriting processes are built within initial teaching formation of PIBID participants. The theoretical and methodological contribution comprised the enunciation-discursive concept of language derived from studies by the Bakhtin Circle, the writing concept as work, within a process perspective which takes into account the revision and rewriting stages from the presuppositions of Applied Linguistics, followed by a research-action as intervention with the participating subjects. Research comprised three main stages: initial diagnosis through a questionnaire; the process of theoretical, methodological and practical formation, or rather, the effective activity as teachers of Basic Education through the production of didactic material and activities within the process of written textual production by Year Six students; final diagnosis similar to the initial one. The following results were the outcome of the registers produced: a) writing, revision and rewriting concepts changed: the teachers understood the concepts through the process stance; revision and rewriting were henceforth understood as recursive and dialogical; b) concepts of correction types were henceforth understood as several possibilities for the intervention in students´ text; c) the rewriting concept revealed that teachers understood that their task was to leave the most adequate text to production conditions and intervene especially through the linguistic and discursive operations of addition, replacement and discarding.